You are on page 1of 22

# !

1. A B A a B
b A B

2. fg f : A B A
B x A
y x x y
y = f (x )
3. f A B
f range { f ( x ) | x A}

1. f : A B B y A
x f onto
2. f : A B A ab f ( a ) f (b)
f one to one
3. f : A B

1-1

1-2

1. 1 + 2 + 3 + L + n =

n( n + 1)
2

2. 12 + 2 2 + 32 + L + n 2 =

n( n + 1)( 2n + 1)
6

n( n + 1)
3. 1 + 2 + 3 + L + n =
2
3

4. ( a b) 2 = a 2 2ab + b 2
5. ( a b) 3 = a 3 3a 2b + 3ab 2 b3
6. a 2 b 2 = ( a b)( a + b)
7. a 3 b3 = ( a b)( a 2 + ab + b 2 )
8. a 3 + b3 = ( a + b)( a 2 ab + b 2 )
9. a n b n = ( a b)( a n 1 + a n 2b + L + abn 2 + b n 1 )

1.
(1)
(2)
(3)
2.
(1)
(2)
3.
4.
5.

1-3

1-4

1-1

1.
x D = {a < x < b} x0 y0
y x y = f (x ) x y

2.
f 2 2 f
f ( x, y , z,L)

1.
y = f (x ) x = g (t ) y = f ( g (t ))

1
y = f ( x ) = x 2 x = g (t ) = f ( g (t )) = ?
t

1
f ( g (t )) =
t

2.
f (x ) g ( y ) D1 , D2 x D1
y D2 g ( f ( x )) = x f ( g ( y )) = y f (x ) g ( y )

f f 1

(1)
f

x1
x2

y1
y2

x3

y3

D1

D2

(2) f f 1 x = y

1.
f (x ) T f ( x + T ) = f ( x ) f (x )
f ( x + T ) = f ( x ) T0

(1) f ( x ) = g ( x ) ,
(2) f ( x ) =

T0
T
<x< 0
2
2

f ( x + T0 ) = f ( x )

g ( x mT )

m =

f (x ) T0 f (kx )

T0

|k |

1-5

1-6

2.
(1)
{ f ( x ) = f ( x ) , x D
| f ( 0) = 0
x 2 k +1 , sin x , tan x , cot x , sin 1 x , tan 1 x ,
sinh x , tanh x ,

(2)
{ f ( x ) = f ( x ) , x D
x 2 k , cos x , cos 1 x , cosh x , | x | ,

(3)
{ =
| =
} = ?
~ =
 =
=

y = f ( x) = x 2 + 2 x + 5

x = g (t ) = e t

t = h( s ) = 2 ln( s )

(1) y = f ( g (t )) = ?
(2) x = g ( h( s )) = ?
(3) y = f ( g ( h( s ))) = ?

2

2

## (3) y = ( e 4[ln( s )] ) 2 + 2( e 4[ln( s )] ) + 5 = e8[ln( s )] + 2e 4[ln( s )] + 5

2

1-7

1-8

(a) y =

x +1
2x 3

(a) y =

(b) y = sinh x

x +1
( 2 x 3) y = x + 1
2x 3

( 2 y 1) x = 1 + 3 y
x =

3y + 1
2 y 1

e x e x
(b) y = sinh x =
2
2 y = e x e x
P = ex

1
= 2y
P

P 2 2 yp 1 = 0
P = ex = y + y2 1
x = ln( y + y 2 + 1)

(a) x 2 cos 5 x

(b) x | x |

## (a) f ( x ) = ( x ) 2 cos(5 x ) = x 2 cos(5 x ) = f ( x )

f (x )

(b) f ( x ) = ( x ) | x |= x | x |= f ( x )
f (x )

f ( x ) f ( x )

f (x )

1-9

1-10

## (a) f ( x ) = x 2 , 1 < x < 2

(b) f ( x ) = x 2 , 2 < x < 2

(a)

f (x )

(b)

f (x )

x = 0

a < x < a

f ( x ) = an x n + an 1 x n 1 + L + a1 x + a0
n ai R

1.
(1) y = f ( x ) = mx + k
y y2
m = 1
( x1 , y1 ), ( x2 , y2 )
x1 x2
x = 0, y = k

(2)
{ m>0

y
x
| m<0

y
x
} m=0

y
x
~ | m |
 m1 = m2
m1 m2 = 1

1-11

1-12

(1) y = 2 x + 5
(2) 2 x + 3 y = 0
(3) y = 2
(4) x = 1

(1)

(2)

(0,5)

(3,2)

5
( ,0)
2

(3)

x
(3,2)

5
2

0
(4)

(0,2)
x

(1,0)

(1)

(2)

2
5

2
2
3

(1) y = x

4
3

(2) y = x + 2

L1 : x + 3 y + 5 = 0
(1) (1,2) L1

(2) y 2 L1
1
3

L1 : y = x

5
3

(1) ( y + 2) = 3( x 1)
1
(2) y = x 2
3

1-13

1-14

2.
(1) y = f ( x ) = ax 2 + bx + c
b 4ac b 2

= a x + +
2a
4a

{ a > 0
a < 0

| b 2 4ac > 0
x1, 2

b b 2 4ac
=
2a

} b 2 4ac 0

f ( x ) = ax 2 + bx + c
x R f ( x ) 0 if a > 0
f ( x ) 0 if a < 0

3.
[ x] = n , n Z , n x < n + 1

4.
x, x 0
| x |=
x, x < 0
(1) | x y |=| x || y | ,

x
|x|
=
y
|y|

(2) | x | | y || x + y || x | + | y |
(3) | x y z || x | + | y | + | z |

1. exponential
(1)
1
x

{ e lim(1 + x ) = 2.718281828
x 0

| y = f ( x) = e x

x
(2)
{ e0 = 1
| ea + b = ea eb ea b = ea / eb
} e ab = ( e a ) b e a / b = b e a
~ lim e x lim e x = 0
x

 x R , e x > 0

1-15

1-16

2. logarithm
(1)

e x = y x = ln( y ) , y > 0

(2)
{ ln(1) = 0
| ln(a ) + ln(b) = ln( ab) ln(a ) ln(b) = ln(a / b)
} ln(a b ) = b ln(a )
~ eln x = x ln(e x ) = x
 ln( x ) x + 1 , x > 0

Hyperbolic

1.
e x e x
(1) sinh( x )
2

sinh x

e x + e x
(2) cosh( x )
2

cosh x

sinh x
(3) tanh( x )
cosh x

tanh x

1
x

1
(4) coth( x )
tanh( x )
(5) sec h( x )

1
cosh( x )

(6) csc h( x )

1
sinh( x )

2.
(1) cosh 2 ( x ) sinh 2 ( x ) = 1
(2) tanh 2 ( x ) + sec h 2 ( x ) = 1
(3) coth 2 ( x ) csc h 2 ( x ) = 1
(4) sinh( x + y ) = sinh x cosh y + cosh x sinh y
(5) cosh( x + y ) = cosh x cosh y + sinh x sinh y

1-17

1-18

3.
(1) sinh 1 ( x ) = ln( x + x 2 + 1) x R

## (2) cosh 1 ( x ) = ln( x + x 2 1) x 1

(3) tanh 1 ( x ) =

1 1+ x
ln
1 < x < 1
2 1 x

(4) coth 1 ( x ) =

1 x +1
ln
| x |> 1
2 x 1

1 + 1 x2
(5) sec h ( x ) = ln

0 < x 1

1
1 + x2

(6) csc h ( x ) = ln +
x
|x|

x 0

1.
a

(1) sin =

a2 + b2

(2) cos =

(3) tan =

a2 + b2

sin
cos

(4) cot( ) =

1
tan

(5) sec( ) =

1
cos

(6) csc =

1
sin

2.
(1)
{ sin( x y ) = sin x cos y cos x sin y
| cos( x y ) = cos x cos y m sin x sin y
tan x tan y
} tan( x y ) =
1 m tan x tan y

1-19

1-20

(2)
{ sin 2 x = 2 sin x cos x
| cos 2 x = 2 cos 2 x 1 = 1 2 sin 2 x = cos 2 x sin 2 x
2 tan x
} tan 2 x =
1 tan 2 x

(3)
{ sin 2

x 1 cos x
=
2
2

| cos 2

x 1 + cos x
=
2
2

} tan

x 1 cos x
sin x
=
=
2
sin x
1 + cos x

(4)
x+ y x y
{ sin x + sin y = 2 sin

cos
2 2
x+ y x y
| sin x sin y = 2 cos

sin
2 2
x+ y x y
} cos x + cos y = 2 cos

cos
2

2
x+ y x y
~ cos x cos y = 2 sin

sin
2

(5)
{ 2 sin x cos y = sin( x + y ) + sin( x y )
| 2 cos x sin y = sin( x + y ) sin( x y )
} 2 cos x cos y = cos( x + y ) + cos( x y )
~ 2 sin x sin y = cos( x + y ) cos( x y )

(6)
a sin x + b cos x = a 2 + b 2 sin( x + )
b
a

= tan 1
(7)
{ cos 2 x + sin 2 x = 1
| tan 2 x + 1 = sec 2 x
} cot 2 x + 1 = csc 2 x

1-21

1-22

1.
sin 1 x = y sin y = x
1 x 1

2.
cos 1 x = y cos y = x
1 x 1 0 y

3.
tan 1 x = y tan y = x
< x <

< y<

4.
cot 1 x = y cot y = x
< x < 0 < y <

5.
sec 1 x = y sec y = x
| x | 1 0 y <

y <

3
2

< y

3
2

6.
csc 1 x = y csc y = x
| x | 1 0 < y